A bidirectional direct current triboelectric nanogenerator with the mechanical rectifier. (January 2021) - Qiao, Guangda; Wang, Jianlong; Yu, Xin; Jia, Rong; Cheng, Tinghai; Wang, Zhong Lin
Abstract: The development of direct current triboelectric nanogenerators (DC-TENGs) is of great significance to powering the electronic devices with low consumption. Thus, a bidirectional direct current triboelectric nanogenerator with the mechanical rectifier (BD-TENG) is proposed in this article, which can convert alternating current (AC) generated in the forward and reversed directions into direct current (DC) output without a bridge rectifier. The BD-TENG is comprised of the mechanical structure component, the triboelectric power-generation unit, and the mechanical rectifier. With the operation of the mechanical structure component, AC output generated by the triboelectric power-generation unit is converted into direct current output with the assistance of the mechanical rectifier. The fluorinated ethylene propylene (FEP) films are fabricated into the micro arch structure in the triboelectric power-generation unit, which can harvest the energy in the forward and reversed directions and reduce the friction and wear between materials. And its optimum width is determined through a series of experiments. In addition, the mechanical rectifier is constitutive of the rolling electric brushes and the commutator, which has the advantages of simple structure and low wear. Finally, the BD-TENG can illumine 210 light-emitting diodes (LEDs) and power a commercial calculator directly due to the DC output. Graphical abstract: Image 1 Highlights: A bidirectional direct current TENG is proposed to realize direct current output without a bridge rectifier. Tribonegative materials are fabricated into the micro arch structure to harvest the mechanical energy in both directions. The mechanical rectifier adopts the structure of rolling electric brush to reduce friction and wear on the commutator.